2019
DOI: 10.14744/bej.2019.70299
|View full text |Cite
|
Sign up to set email alerts
|

Long-TemM Results in Transcanalicular Laser and External Dacryocystorhinostomy

Abstract: This study was an examination of the long-term results of transcanalicular laser (TCL) and external (EX) dacryocystorhinostomy (DCR). Methods: Patients who had undergone TCL-DCR or EX-DCR between 2009 and 2013 were invited for long-term follow-up in 2019. All of the patients who responded had an ophthalmic examination and were assessed using lacrimal irrigation. An intranasal evaluation was performed when the irrigation test had non-patent results. TCL procedures were performed with a diode laser (980 nm). Ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Recently, few studies compared the outcomes of TCLDCR and EXDCR procedures for the treatment of nasolacrimal duct obstructions ( 12 - 15 ). Yener et al ( 15 ) revealed that the functional success rate was 93.2% in EXDCR with a follow-up of 8 years and 85.7% TCLDCR with a follow-up of 7 years. The difference in the success rate was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, few studies compared the outcomes of TCLDCR and EXDCR procedures for the treatment of nasolacrimal duct obstructions ( 12 - 15 ). Yener et al ( 15 ) revealed that the functional success rate was 93.2% in EXDCR with a follow-up of 8 years and 85.7% TCLDCR with a follow-up of 7 years. The difference in the success rate was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Although TCLDCR has been demonstrated to be a safe and effective method in the treatment of nasolacrimal duct obstruction, there are few studies comparing the outcomes of TCLDCR and EXDCR ( 12 - 15 ). Therefore, in the present study, we aimed to compare the results of TCLDCR and EXDCR in the treatment of patients with acquired nasolacrimal duct obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…The success rates of these procedures as reported in the literature vary from 80–95%, 63.3–90.1%, and 57–100%, respectively. [ 1 - 3 ] Although transcutaneous external dacryocystorhinostomy (ExDCR) is still regarded as the gold standard among all, a few studies have shown superior results with the endonasal approach. [ 4 , 5 ] According to a Cochrane database systematic review in 2017, there is little or no difference in success rates between mechanical endonasal DCR and external DCR.…”
mentioning
confidence: 99%